Electrical characterization of copper-based nanowire - Pah, Hazel Pei Lin (2012)
Copper nanowires have been frequently researched due to its outstanding electrical conductivity and low cost. In this project, single crystalline copper nanowires had been successfully fabricated by electrodepositing copper into anodized aluminum oxide. Also, dielectrophoresis (DEP) method was carried out to align the copper nanowires between gold electrodes and after which the aligned nanowires underwent electrical characterization via four-point probing. The resistivity and temperature coefficient of resistance (TCR) were measured and found to be 3560 μΩcm and -0.0103 K-1 respectively. The possible reasons for the high resistivity were contact resistance and copper oxidation. One of the evidences of copper oxidation is the negative TCR value, which is a typical characteristic of a semiconductor; in this case copper oxide is the semiconductor. To further verify that copper had oxidized, the nanowire was stressed at various currents to find out the resistance and current density relationship. An inverse relationship of resistance and current density was obtained and this symbolized a semiconductor characteristic. Hence, it was concluded that the copper nanowire had oxidized and resulted in high measured resistivity. Also, in this project, DEP conditions were studied to find out the optimum peak-to-peak voltage and frequency that will result in the highest number of single aligned nanowires. It was found that the optimum conditions were 5 V and 120 kHz. In the future, ways to reduce nanowire agglomeration can be further explored to ensure lesser bundles and more dispersed nanowires. One of the ways suggested is to induce charges on the surface of nanowires so that nanowires can repel and separate from each other. Also, ways to reduce contact resistance and oxidation of copper nanowires can be looked into so as to reduce the nanowire’s resistivity. Finally, chemical characterization can be carried out to investigate the nanowire’s elemental composition.